Enunciative analysis of discourse genre in protest songs: meeting and social interaction space (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
From a corpus of lyrics, in this paper we analyse protest’s song genre in order to define more common speech acts and polyphony ́s processes. Based on the enunciation theory, protest songs are studied as a result of social dialogue between the addresser and the addressee, whose main objective is the construction of texts with a perlocutionary effect.
Keywords: Enunciative Theory; pragmatics; interaction; protest song